Nanotechnology and manufactured nanomaterials in Latin America and the Caribbean : safety issues (2015)
"Between the 22nd and the 24th of June, 2015, Bogota (Colombia) hosted the Technical Workshop for the Latin American and Caribbean Region on Nanotechnology and Manufactured Nanomaterials: Safety Issues, organized by the United Nations Institute for Training and Research (Unitar), the Organization for Economic Co-operation and Development (oecd), the Ministry of the Environment and Sustainable Development(Colombia), and Universidad of Los Andes, with funding from the Swiss Confederation. Participants included representatives from Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Mexico, Panama, Peru, St. Vincent & the Grenadines, and Uruguay."Página 14